2007
DOI: 10.1007/s00125-007-0823-9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired short-term blood pressure regulation and autonomic dysbalance in children with type 1 diabetes mellitus

Abstract: Aims Because reduction in baroreceptor sensitivity (BRS) has been associated with hypertension in the normal population and with increased cardiovascular morbidity and mortality in patients with diabetes mellitus, we measured BRS in a patient cohort of children with type 1 diabetes mellitus. Methods Two hundred and eight children (150 patients with type 1 diabetes mellitus, mean age 13.9±2.8 years, 70 boys, mean HbA 1c 7.8±1.4%; and 58 healthy controls, mean age 14.1±3.1 years, 32 boys) were studied. BRS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Improved glycemic control slows the progression of DM [84] and should therefore improve prognosis in such patients. BRS has also been correlated with HbA1c level [82].…”
Section: Clinical and Prognostic Consequences Of Diminished Brs (Seementioning
confidence: 99%
See 2 more Smart Citations
“…Improved glycemic control slows the progression of DM [84] and should therefore improve prognosis in such patients. BRS has also been correlated with HbA1c level [82].…”
Section: Clinical and Prognostic Consequences Of Diminished Brs (Seementioning
confidence: 99%
“…Female diabetic patients have been shown to have lower BRS and worse prognosis than their male counterparts [81]. Also, there exists a negative correlation between the disease duration and the BRS in diabetic patients [82]. Studies in DM patients have demonstrated that the degree of autonomic (sympathovagal) imbalance determines the extent of BRS impairment [82].…”
Section: Clinical and Prognostic Consequences Of Diminished Brs (Seementioning
confidence: 99%
See 1 more Smart Citation
“…Also the relation between exercise and decreased sympathetic activity has been suggested (Billman, 2002). Impaired cardiovascular ANS function has been associated with type 1 diabetes (T1D) (Ziegler et al, 2001; Riihimaa et al, 2002; Dalla Pozza et al, 2007; Lucini et al, 2009; Rosengård-Bärlund et al, 2009; Spallone et al, 2011; Kuehl and Stevens, 2012). Recently, we reported lower aerobic capacity (VO 2peak ) in Type 1 diabetes patients than in healthy controls (Peltonen et al, 2012), which is in agreement with several other papers (Niranjan et al, 1997; Komatsu et al, 2005; Gusso et al, 2008; Nadeau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While there appears to be no direct investigations of perivascular sympathetic nerves in human diabetics, there are reports of increased, rather than decreased, sympathetic vasomotor regulation in young type 1 diabetics (e.g., Dalla Pozza et al, 2007; Lucini et al, 2009). In addition, a number of studies have reported that reductions in parasympathetic control of the heart in type 1 diabetic patients precede impairment of sympathetic vasomotor regulation (e.g., Javorka et al, 2005; Dalla Pozza et al, 2007). These findings suggest vasoconstrictor sympathetic neurons are less vulnerable to the neurotoxic effects of Type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%